Stereoselective Ketamine Metabolism by Genetic Variants of Cytochrome P450 CYP2B6 and Cytochrome P450 Oxidoreductase. (October 2018) - Wang, Pan-Fen; Neiner, Alicia; Kharasch, Evan D.
Editor's Perspective: What We Already Know about This Topic: Ketamine is metabolized to both active and inactive metabolites by cytochrome P4502B6 (CYP2B6), which is assisted by P450 oxidoreductase CYP2B6 and by P450 oxidoreductase are highly polymorphic, with many genetic variants What This Article Tells Us That Is New: Several genetic variants of CYP2B6 and P450 oxidoreductase have diminished ketamine N -demethylation activity Variants do not have altered stereoselectivity of ketamine metabolism Results suggest candidate polymorphisms of CYP2B6 and P450 oxidoreductase for clinical evaluation Background: Human ketamine N -demethylation to norketamine in vitro at therapeutic concentrations is catalyzed predominantly by the cytochrome P4502B6 isoform (CYP2B6). The CYP2B6 gene is highly polymorphic. CYP2B6.6, the protein encoded by the common variant allele CYP2B6*6, exhibits diminished ketamine metabolism in vitro compared with wild-type CYP2B6.1. The gene for cytochrome P450 oxidoreductase (POR), an obligatory P450 coenzyme, is also polymorphic. This investigation evaluated ketamine metabolism by genetic variants of human CYP2B6 and POR . Methods: CYP2B6 (and variants), POR (and variants), and cytochrome b 5 (wild-type) were coexpressed in a cell system. All CYP2B6 variants were expressed with wild-type POR and b 5 . All POR variants were expressed with wild-type CYP2B6.1 and b 5 . Metabolism of R - and S -ketamine enantiomers, and racemic RS -ketamine to norketamine enantiomers, was determined using stereoselective high-pressure liquid chromatography–mass spectrometry. Michaelis–Menten kinetic parameters were determined. Results: For ketamine enantiomers and racemate, metabolism (intrinsic clearance) was generally wild-type CYP2B6.1 > CYP2B6.4 > CYP2B6.26, CYP2B6.19, CYP2B6.17, CYP2B6.6 > CYP2B6.5, CYP2B6.7 > CYP2B6.9. CYP2B6.16 and CYP2B6.18 were essentially inactive. Activity of several CYP2B6 variants was less than half that of CYP2B6.1. CYP2B6.9 was 15 to 35% that of CYP2B6.1. The order of metabolism was wild-type POR.1 > POR.28, P228L > POR.5. CYP2B6 variants had more influence than POR variants on ketamine metabolism. Neither CYP2B6 nor POR variants affected the stereoselectivity of ketamine metabolism ( S > R ). Conclusions: Genetic variants of CYP2B6 and P450 oxidoreductase have diminished ketamine N -demethylation activity, without affecting the stereoselectivity of metabolism. These results suggest candidate genetic polymorphisms of CYP2B6 and P450 oxidoreductase for clinical evaluation to assess consequences for ketamine pharmacokinetics, elimination, bioactivation, and therapeutic effects. Abstract : Several genetic variants of CYP2B6 and P450 oxidoreductase have diminished ketamine N -demethylation activity. Variants do not have altered stereoselectivity of ketamine metabolism. Results suggest candidate polymorphisms of CYP2B6 and P450 oxidoreductase for clinical evaluation.